Analisis potensi dan tantangan dalam memajukan wisata di rawa bento Kecamatan Gunung Tujuh, Kabupaten Kerinci, Provinsi Jambi - Ricky Ishadi; Johannes Johannes; Husni Hasbullah (Prodi Magister Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2020)
This study aims to analyze the strengths, weaknesses, opportunities, and threats of BUMDES Jernih Jaya in developing the natural tourism object of Rawa Bento, Kerinci Regency, Jambi Province. Then formulate a strategy for development by minimizing weaknesses and threats, maximizing utilization of opportunities and strengths. Data was collected through literature study, observation, and interviews with stakeholders, namely BUMDES and village heads. The data were analyzed descriptively and then to determine the strategy for developing natural attractions in Bento Swamp. A SWOT analysis was carried out. Based on the results of the research, it can be concluded that the strategy for developing natural attractions in Rawa Bento includes building infrastructure such as road access, transportation means, and accommodation facilities, making tourist attractions and promoting tourism objects, developing tourism products, and involving the community in tourism management.